Pengembangan Usaha Kerajinan Clay Melalui Strategi Pemasaran Digital dan Offline - Darren Nataleano Metusalak Taulo; Khosnol Khotimah; Melkior Keleka Hayon; Muhammad Yasin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This proposal discusses a business plan for handcrafted products made from clay, focusing on cup holders and ashtrays with unique and eco-friendly designs. Clay is chosen as the main material due to its high flexibility, aesthetic value, and broad market potential. The purpose of this business is to create decorative yet functional products that are customizable and appealing to various groups, particularly art lovers and handmade product enthusiasts. The methods used include market analysis through questionnaires, digital and offline marketing strategies, and a Business to Customer (B2C) approach. Survey results indicate strong consumer interest in clay tray products, driven by affordable pricing, attractive designs, and eco-friendly qualities. Promotional strategies include social media, online marketplaces, participation in exhibitions, and collaborations with influencers. This proposal also includes a financial analysis to determine the break-even point (BEP) and assess the business's profit potential. With proper management, this clay craft business is considered to have promising prospects and the potential to grow into a sustainable enterprise..